Private Ordering and the Creation of International Copyright Norms: The Role of Public Structuring - Dinwoodie, G (2004)
International copyright law must be based on an assessment of what types and levels of protection best further the purposes of copyright law. But constructing the international copyright regime is difficult as the international system must wrestle with copyright dilemmas that exist at the national level as well as broader challenges facing international law. This paper delineates the connection between international copyright law and the generation and distribution of knowledge by discussing two recent examples of (possible) unconventional international copyright rulemaking, namely, norms generated by Internet Service Providers in responding to infringement claims, and norms arising out of digital rights management systems. (JEL: K 29).